2020
DOI: 10.1111/jon.12827
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Transcriptomics in Neurodegenerative Diseases

Abstract: Imaging transcriptomics investigates the relationship between neuroanatomical/neuroimaging features and gene expression. The spatial and temporal distribution of the expressed genes and their pattern of spreading over time can contribute to elucidating cellular and molecular processes involved in neurodegeneration. In this study, we review recent findings regarding the correlation between neuroimaging and expression data in neurodegenerative diseases with a focus on Alzheimer's disease and Parkinson's disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Abbreviation: TF, transcription factor. studying neurodegenerative changes at single-cell resolution is the rapidly maturing field of spatial transcriptomics [119,[121][122][123]. Leveraging the twin powers of oligonucleotide-based barcoding and in situ hybridization, numerous recent studies have demonstrated simultaneous recognition of hundreds to thousands of RNA species in morphologically intact brain tissue [18,19,124].…”
Section: Trends Trends In In Genetics Geneticsmentioning
confidence: 99%
“…Abbreviation: TF, transcription factor. studying neurodegenerative changes at single-cell resolution is the rapidly maturing field of spatial transcriptomics [119,[121][122][123]. Leveraging the twin powers of oligonucleotide-based barcoding and in situ hybridization, numerous recent studies have demonstrated simultaneous recognition of hundreds to thousands of RNA species in morphologically intact brain tissue [18,19,124].…”
Section: Trends Trends In In Genetics Geneticsmentioning
confidence: 99%
“…Prior studies of brain size have primarily relied on in vivo neuroimaging, which have been only indirectly linked with brain gene expression because of the relative inaccessibility of in vivo human brain tissue. The burgeoning field of "imaging-transcriptomics" [68][69][70] has demonstrated a high degree of spatial alignment between neuroimaging "gradients" -representing topographical variation of brain morphology, function, or connectivity typically derived from magnetic resonance imaging (MRI) data [71][72][73] -and the spatial topography of gene expression identified in highresolution transcriptomic resources such as the Allen Human Brain Atlas (AHBA) 25,[74][75][76][77] . However, only one previous study has directly examined brain size and brain gene expression using the comprehensive Allen Mouse Brain Atlas 78 , finding a robust power-law scaling relationship between spatial gene expression gradients and brain size across mouse development -a model which accurately predicted human brain size 79 .…”
Section: Discussionmentioning
confidence: 99%
“…These include susceptibility-weighted imaging (SWI), magnetic resonance spectroscopy (MRS) and perfusion-based MRI to, name a few (see [ 22 ]). Intriguing advances in imaging transcriptomics are leading the way to identify genomic alterations that correlate to neuroimaging measures [ 57 ]. In summary, multimodal MRI for the study of MCI and AD provides diagnostic information on the progression of disease, whereby clinicians and investigators alike can select the appropriate imaging sequence(s) based on the question being probed.…”
Section: Human Imaging Of Alzheimer’s Disease: Brief Overviewmentioning
confidence: 99%